A Critical Review of Recent Scholarship on the Pauline Opposition and the Nature of its Wisdom (σοϕί α) in 1 Corinthians 1—4 - Kwon, Oh-Young (Currents in biblical research, 2010)
In recent scholarship Pauline scholars have hotly disputed the issues of identification of Paul’s opponents in 1 Cor. 1—4 and the nature of their σοϕία. The major hypotheses are summarized by the catchphrases: over-realized eschatology, proto-Gnosticism, Hellenistic Jewish wisdom tradition, the Petrine party, and rhetorical conventions. Of these hypotheses, this paper supports those scholars who investigate the identity of Paul’s Corinthian opponents in 1 Cor. 1—4 and the nature of their wisdom from the perspective of first-century Graeco-Roman culture. These scholars argue that the Pauline opposition in 1 Cor. 1—4 would have been a group of Corinthian Christians who were influenced by Graeco-Roman rhetorical elitism and uncritically exercised these rhetorical conventions in their Christian community and claimed their σοϕία to be based on these rhetorical patterns.